Pengaruh Pelatihan Manajemen Nyeri terhadap Peningkatan Kompetensi Perawat - Adriyanti Amran; Widianingsih Widianingsih; Syamsul Anwar (Jurnal Keperawatan Silampari, 2019)
The purpose of this study was to analyze the effect of pain management training on improving nurses' competency in adult diseases in Padang Pariaman hospital. The Method This study uses a quasi-experimental design with one group pre-post test design approach. The results of this study obtained statistically shows that there is an increase in the cognitive, affective and skills of pain management by nurses (p <0.05). Variable knowledge of nurses increased with a value of 8,647 Â± 3,427, attitudes 7,882 Â± 3,789 and skills 14,06 to 16,76. The conclusion of this study that Off the job training is very potential for improving nurse competence in pain management, especially in improving cognitive competence, effectiveness, and pain management skills. Continuous training and evaluation of the application of pain management are expected to improve the ability of nurses to carry out pain management. Keywords: Pain Management Training, Cognitive, Affective, Skill, Competence